HPV Prophylactic Vaccination in Males Improves the Clearance of Semen Infection() - Foresta, Carlo (EBioMedicine, 2015)
BACKGROUND: Semen represents a reservoir for human papillomavirus (HPV), rising concern in couples eligible for assisted reproduction techniques (ART). Humoral immunity against HPV is considered to protect from reinfection. We investigated the impact of vaccination on virus clearance in a cohort of infertile male patients showing HPV semen infection. METHODS: 179 out of 619 infertile patients, showing HPV-DNA detection in semen by FISH analysis, were enrolled. Subjects were split into 91 vaccine-sensitive (VSPs) and 88 nonvaccine-sensitive patients (NVSPs) by INNO-LiPA. 19 VSPs showed vaccine-type specific seroconvesion at recruitment. All patients underwent specific counselling. 42 seronegative VSPs were randomly assigned to receive quadrivalent vaccination in 6 months, whilst 49 VSPs, 19 seroconverted and 30 seronegative, served as controls. The prevalence of HPV-DNA semen infection and serology was studied in a follow-up of 24 months. RESULTS: Compared to seronegative patients, VSP seroconverted at recruitment showed absence of multiple infections and reduced prevalence of HPV semen infection at 12 (P = 0.039), 18 (P = 0.034) and 24 months (P = 0.034) of follow-up. Vaccinated VSP showed improved healing (P = 0.001 at 6 months and P < 0.001 at 12 months vs seroconverted VSP), achieving clearance in 12 months. DISCUSSION: Humoral immunity has a major role in healing from HPV infection. Elder ART patients with HPV semen infection may benefit by the union of both specific counselling and available prophylactic vaccination.